2016
DOI: 10.1016/j.compstruct.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations and variability considerations on 3D interlock textile composites used in low velocity soft impact loading

Abstract: a b s t r a c tThis study investigates the performance of three-dimensional (3-D) woven interlock composite plates subjected to impact loading. Low velocity (lower than 10 mÁs À1 ) impacts with highly deformable rubber impactor are addressed. Response variability is investigated by conducting several impact tests in the same conditions. The effect of mass and velocity on damage tolerance is studied by varying the impact conditions. Force-time, displacement-time and force-displacement curves are first analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Therefore, since the past four decades there has been a growing interest in the development of several methods in order to provide through-thickness strength and stiffness to preforms in the three-dimensional (3D) direction using through the thickness reinforcement techniques [5] [6] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, since the past four decades there has been a growing interest in the development of several methods in order to provide through-thickness strength and stiffness to preforms in the three-dimensional (3D) direction using through the thickness reinforcement techniques [5] [6] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…The need for affordable composites that have significantly improved through-thickness strength and interlaminar damage tolerance intensified the development of a wide variety of textile preforms [4]. A variety of 3D fibre composites have been developed to overcome some of the problems that are inherent with conventional polymer laminates, such as their low delamination resistance and poor impact damage tolerance [58]. Especially the through-thickness fibres, which are given the general term of z-binders, are used to provide 3D fibre composites with higher delamination fracture toughness and impact damage tolerance than conventional laminates [911].…”
Section: Introductionmentioning
confidence: 99%
“…34 The load-time, displacement-time, and load-displacement curves during low-velocity impact allowed to identify a critical threshold energy for the composite material perforation. 35 3D (X-ray tomography) imaging of 3D LL and angle interlock (AI) showed that, higher crack density was found in the angle interlock composite than the LL composite. Transverse cracking is initiated in the fiber-rich regions of weft yarns rather than the resin-rich regions 36 and greatly affected by the void volume fraction.…”
Section: Introductionmentioning
confidence: 99%